2019
DOI: 10.1590/1414-431x20198324
|View full text |Cite
|
Sign up to set email alerts
|

The role of KDR in intrauterine adhesions may involve the TGF-β1/Smads signaling pathway

Abstract: The aim of this study was to investigate the role of kinase-insert domain-containing receptor (KDR) in intrauterine adhesions (IUA) and its mechanism. The Case group consisted of 92 patients diagnosed with IUA, and the Control group included 86 patients with uterine septum who had normal endometrium verified with an uteroscope. In addition, 50 rats were randomly assigned into Control, Sham, Model, NC-siRNA, and KDR-siRNA groups. Rats in the Model, NC-siRNA, and KDR-siRNA groups were induced by uterine curettag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
(38 reference statements)
1
13
0
Order By: Relevance
“…In consistence with the previous studies [ 58 , 59 ], our results demonstrated that the mRNA expression of VEGF in endometrium in the UCMSC-AAM group decreased compared with the injury group and AAM group, higher than that of the normal group, indicating the mitigation of fibrosis after transplantation of UCMSC-AAM. It is reported that the expression of VEGF can be regulated by various growth factors and cytokines (EGF, TGF β , PGE2, IL-1, IL-6) [ 60 ].…”
Section: Discussionsupporting
confidence: 91%
“…In consistence with the previous studies [ 58 , 59 ], our results demonstrated that the mRNA expression of VEGF in endometrium in the UCMSC-AAM group decreased compared with the injury group and AAM group, higher than that of the normal group, indicating the mitigation of fibrosis after transplantation of UCMSC-AAM. It is reported that the expression of VEGF can be regulated by various growth factors and cytokines (EGF, TGF β , PGE2, IL-1, IL-6) [ 60 ].…”
Section: Discussionsupporting
confidence: 91%
“…Many strategies or principles for decreasing the risk of developing IUA, such as the reduced use of electrosurgery and the minimization of trauma to the healthy endometrium and myometrium, have been proposed [ 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. Additionally, many biomaterial agents, barrier methods, and cell or bio-agent therapies have been applied [ 14 , 16 , 24 , 27 , 28 , 29 , 30 , 31 , 35 , 37 , 40 , 43 , 44 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. Figure 3 shows the recent development of agents available for the primary prevention of IUA after uterine surgery.…”
Section: Primary Prevention Of Intrauterine Adhesion (Iua)mentioning
confidence: 99%
“…One involves the avoidance of over- or purulent inflammatory processes or over-traumatic injury; the second is a barrier method to prevent the attachment of the bilateral traumatic surface; the third is the enhancement of regeneration ability; the last is early intervention via repeat hysteroscopy to remove the thin or immature adhesion band ( Figure 3 ). The tools include agents (drugs) or physical (mechanical) barriers to cover the uterine lining side, or separate the opposing sides of the uterine linings immediately after hysteroscopic surgery; the prescription of estrogen use postoperatively, postoperative gonadotropin-releasing hormone agonist injection, or immediate postoperative antibiotics use; and the use of biomaterials or new technologies such as cellular therapy [ 5 , 6 , 7 , 8 , 9 , 10 , 14 , 23 , 24 , 27 , 28 , 29 , 30 , 31 , 32 , 35 , 36 , 37 , 39 , 40 , 41 , 42 , 43 , 56 , 57 , 58 , 59 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 86 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , …”
Section: Primary Prevention Of Intrauterine Adhesion (Iua)mentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [ 33 ] also reported that NF-κB was highly expressed in endometrial tissues of IUA patients and therefore a putative pathogenic factor for IUA. Chen et al [ 30 ] found that the expression of KDR in IUA tissues was significantly higher than that of the normal counterpart, and also the expression of KDR was positively correlated with the severity of IUA. Silencing KDR could upregulate MMP-9 and affect TGF-β1/SMAD pathway to inhibit the occurrence and development of IUA, so KDR was thought to play an important role in the formation of IUA.…”
Section: Iua Pathogenesismentioning
confidence: 99%